Pelatihan Manajemen Aplikasi Perplexity dalam Penyusunan Artikel Ilmiah Mahasiswa MPI Universitas Nurul Jadid - Moh. Rofiki; M. Idris Yamin; Muhammad Ali Ghufron; Moh Mufid (Universitas Kristen Indonesia Toraja, 2024)
Many researchers, including lecturers, teachers, students, and the general public, have adopted apps to help them write articles. Students are currently expected to produce scientific articles published in accredited journals or respected international journals as part of their final assignment. However, from the observations of the service team, there are several problems faced by the service partners, especially MPI students. They have difficulty preparing scientific article manuscripts and are less familiar with applications that can speed up the preparation process. To overcome this, the service was carried out through lecture, discussion, and mentoring methods using service-learning, which involved pre-implementation, implementation, and post-implementation stages. The results of this service showed that the training provided participants with understanding and knowledge about using the Perplexity application as a tool to speed up the preparation of articles and paraphrasing to avoid plagiarism. This is evident from the comparison of the participants' pre-test and post-test results before and after the training.